Impact of downsizing, restructuring and knowledge sharing on retention of knowledge in organisations : implications for organisational effectiveness - Sitlington, Helen (Curtin University, 2008)
This research considers the organisational factors and processes that impact on knowledge retention and subsequent perceptions of organisational effectiveness during downsizing/restructuring events. By exploring these relationships, the research seeks to help organisations facing downsizing/restructuring to identify best practices to support employees during the process and achieve positive organisational outcomes. The thesis presents a detailed review of the literature in the field of downsizing and organisational restructuring, together with knowledge, knowledge sharing and organisational effectiveness. A conceptual framework and hypotheses, informed through the literature and qualitative focus group process, were developed for testing. Data were collected from 81 organisations, drawn from both the private and public sectors. Analyses enabled detailed consideration of the impact of perceived levels of organisational knowledge on perceptions of post-downsizing/restructuring organisational effectiveness. The significance of relationships between downsizing/restructuring events, both decisions and processes, and knowledge sharing in organisations undergoing downsizing/restructuring were also examined. Findings indicate the need for open and honest relationships between managerial (Decision Makers and Implementers) and non-managerial employees (Affected Employees) in order to achieve successful organisational outcomes. The impact of knowledge sharing on organisational knowledge was assessed by studying the extent of both formal knowledge sharing and informal networks present in respondent organisations. The direct impact of knowledge sharing on organisational outcomes was also analysed and discussed.Conclusions are reached that both formal knowledge sharing and informal networks have a significant impact not only on perceived levels of organisational knowledge but also on post-downsizing/restructuring organisational effectiveness. However, different aspects of knowledge sharing appear to be more significant to Decision Makers and Implementers and Affected Employees. For business, the findings of this research demonstrate a need to concentrate on organisational knowledge during downsizing/restructuring in order to achieve improved outcomes. The findings suggest this can be done through attention to ensuring that intent and interpretation of the decisions and processes involved are open and honest. Assessment of the knowledge present in the organisation and a focus on retention of key individuals with important knowledge is also advisable. Communication of what is planned and inclusion of employees in both planning and implementation were identified as ways in which organisations can do so, thereby promoting distributive and procedural fairness throughout the process. Formal knowledge sharing strategies arose as being important to achieving improved organisational outcomes, particularly to Decision Makers and Implementers. These strategies included identifying, capturing and storing information in ways that are accessible to employees. Documentation of practices and procedures was also found to be important as was careful planning of the change.Communication, providing training and support to survivors and allowing the necessary time for sharing knowledge were also identified as key strategies. Overall, developing a culture and climate within the organisation that is supportive of knowledge sharing was found to be central to achieving improved organisational effectiveness. Informal networks were identified by Affected Employees as impacting on both perceived levels of organisational knowledge and, indirectly on organisational outcomes. The research indicates the Decision Makers and Implementers and Affected Employees have different perceptions about the role and importance of informal networks. Those implementing downsizing/restructuring may therefore need to examine the structure and operation of informal networks prior to downsizing/restructuring to ensure they are adequately supported during the process. Informal networks may also be utilised to assist in bringing about the change. The findings of this research are important to assist organisations develop best practice approaches to downsizing/restructuring. With increasing acceptance of downsizing/restructuring as a business strategy, this research provides insights into key issues of downsizing/restructuring events and knowledge retention as predictors of improved organisational outcomes.